Cholesterotic Fibrous Histiocytoma in a Patient with Metabolic Syndrome - Masatoshi Deguchi; Setsuya Aiba (Karger Publishers, 2017)
Among the many variants of dermatofibroma, dermatofibroma with cholesterol cleft (cholesterotic fibrous histiocytoma) is extremely rare. Here, we describe the case of a 50-year-old male patient with a cholesterotic fibrous histiocytoma on his left lower leg. He presented with a hyperkeratotic nodule 6 mm in diameter with a brown surface on the extensor surface of his left lower leg. The lesion had developed over the course of a few years without any tendency to heal. A skin biopsy performed on the tumor showed histopathological findings compatible with those of dermatofibroma. Interestingly, the lesion included many cholesterol clefts, as well as foamy histiocytes and multinucleated giant cells around them. He had had metabolic syndrome for years. To the best of our knowledge, this is the first report of a cholesterotic fibrous histiocytoma in a patient with metabolic syndrome. We conclude that the altered microenvironment caused by metabolic syndrome, as well as hyperlipoproteinemia itself, may play a role in the pathogenesis of this rare case.